DISCOVERING MACEDONIAN RED-FIGURE POTTERY: A NEW PELIKE ATTRIBUTED TO THE PELLA WORKSHOP. (16th January 2015) - Akamatis, Nikos
<x content-type="archive" xml:space="preserve">Abstract</x> The question of the appearance, operating conditions and diffusion of the products of local red-figure pottery workshops in the fourth century bc, in conjunction with the spread of Attic red-figure ware and its influence on local potteries, has been a focus of research in recent years. The result has been the recognition of a number of local workshops all across Greece, including those of Chalcidice, Boeotia, Euboea, Corinth, Elis, Sparta, Crete and the Agrinion Group. This article examines a red-figure pelike made by a previously unknown local workshop that was very likely located in Pella, the capital of the Kingdom of Macedonia. This vessel was in storage in the Archaeological Museum of Thessaloniki and is one of the best-preserved examples from that Macedonian workshop. In shape and decoration it recalls Attic vases of the second half of the fourth century bc, and particularly the work of Group G and the Amazon Painter. The pelike dates from c.320 bc and is attributed to the Pella B Painter.